Simulation of a 2-dimensional coupled vane compressor - Tan, Kimberly Ting Hui (Nanyang Technological University, 2020)
The coupled vane compressor (CVC) was designed with a smaller rotor-to-cylinder ratio (compared to other positive rotary compressors) for compactness, with the aim to reduce material usage and carbon footprint. This report presents on the setup of the 2-dimensional model of the CVC for CFD studies. The setup includes deriving geometrical and kinematic models, choosing appropriate dynamic mesh methods and turbulence models for the simulation of the CVC. The difference in various dynamic mesh methods was presented through a CFD study done on the compression process in a reciprocating compressor, as it is simpler, and takes a shorter time to run. A comparative study of various operating conditions was carried out, to understand the factors which affect the pressure and pressure ratio of the CVC. Unsteady vortices were also observed in the suction port, compression chamber and the discharge port. Circulation due to the leakage decreases the inflow and causes vibrations at the inlet port. This study has added new insights into the gas activities in the working chamber of the compressor.